Дух любви: роман / Дафна Дю Морье - Дю Морье Дафна (Амфора, 2002)
Экземпляры: ФИЛ (20040514) / Инвентарный номер: 1050306 / Цена: 127.50 / Сис.шифр: И(Англ) / Авт.знак: Д 95 / ГРНТИ: 17 / ББК: 84(4/8)